Migration and deforestation in Indonesia - Rivayani Darmawan; Stephan Klasen; Nunung Nuryartono (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2016)
Indonesia now has the highest deforestation rate in the world, with an average increase of about 47,600 ha per year. As a result, the nation is one of the largest emitters of greenhouse gases in the world and is putting its rich biodiversity at risk. Although the literature discussing the political economy of Indonesia commercial's logging is growing, only a small amount focuses on the relation-ship between migration and deforestation. Migration may contribute to the forest cover change, as migrants often face serious constraints from the local residents in claiming the land, and thus tend to find new forest land which can be used as a means of living or converted into an agricultural planta-tion. This paper empirically investigates the relationship between recent in-migration and deforestation in Indonesia. By combining available population census data with the satellite image data MODIS, we find a significant positive relationship between migration and deforestation at the district level using a fixed effects panel econometric framework. The results also suggest that the expanding oil palm production is one significant driver for the fast disappearance of Indonesia's forest.
urn:nbn:de:gbv:7-webdoc-3967-7
Keywords: Q23; R14; J61; 330; deforestation; migration; oil palm; Indonesia